2022
DOI: 10.1186/s13690-022-00813-6
|View full text |Cite
|
Sign up to set email alerts
|

Geotemporospatial and causal inferential epidemiological overview and survey of USA cannabis, cannabidiol and cannabinoid genotoxicity expressed in cancer incidence 2003–2017: part 3 – spatiotemporal, multivariable and causal inferential pathfinding and exploratory analyses of prostate and ovarian cancers

Abstract: Background The epidemiology of cannabinoid-related cancerogenesis has not been studied with cutting edge epidemiological techniques. Building on earlier bivariate papers in this series we aimed to conduct pathfinding studies to address this gap in two tumours of the reproductive tract, prostate and ovarian cancer. Methods Age-standardized cancer incidence data for 28 tumour types (including “All (non-skin) Cancer”) was sourced from Centres for Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 169 publications
4
18
0
Order By: Relevance
“…A note should be given to the publication [ 69 ] that suggested, based on an epidemiological overview and survey of USA cannabis and cannabinoid users, that CBD might be considered a community carcinogen, additive to the effects of tobacco. Due to the considerable effect of CBD on cancer-associated genetic pathways, adverse effects from activating these pathways are possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A note should be given to the publication [ 69 ] that suggested, based on an epidemiological overview and survey of USA cannabis and cannabinoid users, that CBD might be considered a community carcinogen, additive to the effects of tobacco. Due to the considerable effect of CBD on cancer-associated genetic pathways, adverse effects from activating these pathways are possible.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the actual cannabis molecules and their combination(s) that might be active against OC markers have not been identified. In contrast, an epidemiological overview and survey of cannabis and phytocannabinoid users in the USA between 2003 and 2017 on the occurrence of prostate and ovarian cancers suggested that CBD might be considered a community carcinogen, additive to the effects of tobacco [ 69 ].…”
Section: Studies That Have Examined the Effectivity Of Cannabis Compo...mentioning
confidence: 99%
“…The concern is that this relatively abrupt launching of parts of the continent into higher cannabinoid exposure zones will continue to see an increasing number of severe genotoxic outcomes such as those described above for amelia. Particularly when this report is read in conjunction with other reports on cannabinoid teratogenicity [ 4 , 5 , 6 , 7 , 11 , 16 , 108 , 130 , 131 ], cannabinoid cancerogenicity [ 95 , 96 , 97 , 99 , 100 , 102 , 103 , 104 , 106 , 108 ], cannabinoid accelerated aging [ 102 , 132 , 133 ], heritable mutagenic and carcinogenic disease [ 98 , 99 , 100 , 108 , 134 , 135 , 136 ], and heritable neurotoxicity [ 107 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ], it becomes clear that rational policies in this area would tightly restrict and control community exposure to genotoxic and neurotoxic cannabinoids for multiple public health indications as has always been the community’s response to known serious genotoxic xenobiotics. The prospect of continued contamination of the food chain and increasing population exposure, incurring avoidable genetic and epigenetic damage to the heritable material of the population for multiple generations to come, is most serious indeed.…”
Section: Discussionmentioning
confidence: 93%
“…As outlined in the introduction, the mechanisms of cannabis genotoxicity are many and complex and have been reviewed elsewhere [ 4 , 5 , 6 , 7 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. For our present purposes, we wish to focus on two pathways of particular importance, these being the disruption of key morphogen gradients and the epigenomic perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, strong epidemiological evidence from many jurisdictions showed the likely involvement of cannabinoids in many cancers, dozens of serious birth defects and cellular and organismal aging [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Moreover, there is a remarkably close uniformity between the findings from different jurisdictions [ 38 , 39 ], which not only confirms the findings of single studies but also, according to the established Hill criteria of causality, lends formal credence to the likely causal relationship between epidemiologically assessed cannabis exposure and the observed morbidity.…”
Section: Introductionmentioning
confidence: 99%